Molecular evidence to suggest the origien of a colonization: Drosophila suboscura in América - Araúz, Pedro (Universidad Especializada de las Américas, 2020)
The recent colonization of America by Drosophila subobscura represents a great opportunity for evolutionary biology studies. Knowledge of the populations from which the colonization started would provide an understanding of how genetic compo- sition changed during adaptation to the new environment. Thus, a 793 nucleotide frag- ment of the Odh (Octanol dehydrogenase) gene was sequenced in 66 chromosomal lines from Barcelona (western Mediterranean) and in 66 from Mt. Parnes (Greece, eastern Mediterranean). No sequence of Odh fragment in Barcelona or Mt. Parnes was identical to any of those previously detected in America. However, an Odh sequence from Bar- celona differed in only one nucleotide from another found in American populations. In both cases, the chromosomal lines presented the same inversion: O , and the Odh gene was located within this inversion. This evidence suggests a possible western Mediter- ranean origin for the colonization. Finally, the molecular and inversion data indicate that the colonization was not characterized by multiple reintroductions.